1976
DOI: 10.1007/bf00582892
|View full text |Cite
|
Sign up to set email alerts
|

The decomposition of branch-wood in the canopy and floor of a mixed deciduous woodland

Abstract: The pattern of decomposition of branch-wood greater than 2 cm diameter is described for a one hectare site at Meathop Wood, Cumbria, based on studies carried out as part of the IBP between 1967 and 1972. Three phases of decomposition are recognised. Following the death of branches in the canopy and their colonisation by fungi, decomposition proceeded at an average annual loss rate of about 8.4%. Wood at branch-fall had on average lost about 40% of its original dry weight. On the forest floor the average annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 7 publications
2
24
2
Order By: Relevance
“…The differences in the decomposition rates among tree species can be attributed to differences in the initial chemical composition of the branches, since litter quality is an important factor that determines the rates of C and nutrient turnover [7,55,56]. Our results also indicated that each tree species differed in its initial chemical composition and that the decomposition rate was significantly correlated with each parameter of litter quality ( Figure 3).…”
Section: Discussionmentioning
confidence: 58%
“…The differences in the decomposition rates among tree species can be attributed to differences in the initial chemical composition of the branches, since litter quality is an important factor that determines the rates of C and nutrient turnover [7,55,56]. Our results also indicated that each tree species differed in its initial chemical composition and that the decomposition rate was significantly correlated with each parameter of litter quality ( Figure 3).…”
Section: Discussionmentioning
confidence: 58%
“…However, due to the preconditioning of most wood before entering streams in nature (Swift et al 1976), it seems to be more important that the present method works well for preconditioned wood. Nevertheless, it remains unknown whether it is closer to natural conditions to use prewetted or dry wood for investigation of processes related to submerged wood in aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 97%
“…The water content of fallen wood is influenced by rainfall before abscission and by the humidity of the soil on which the particular branch lay. Branches entering the streams by litterfall or lateral input from the forest floor are often preconditioned (Swift et al 1976) and moistened (Boddy 1983). …”
mentioning
confidence: 99%
“…comrn.) cloud cover is expressed as the ratio of actual hours of bright sunshine, n, to the maximum possible sunshine hours, N. Therefore we use the Angstrom relationship in the following way (Swift et al 1976, Jones 1992, Fnend pers. comm.…”
Section: Cass = U Lai(gc)hl[ilai(gc)]h2(t)-h7(sw)mentioning
confidence: 99%